Geschlechterreflektierte Professionalisierung : Geschlecht und Professionalität in pädagogischen Berufen (Verlag Barbara Budrich, 2019)
Against the background of various gender-theoretical and empirical approaches, the 15th volume of the yearbook "Educational Gender Research" (formerly: Women's and Gender Research in Educational Science) makes tangible the challenges of gender-reflective or gender-reflective professionalism and practices in training and further education as well as in professional Action practice pedagogically active visible.